2010
DOI: 10.1111/j.1540-4560.2010.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the Contact-Prejudice Relation among South African Students on Four University Campuses

Abstract: Intergroup contact is undoubtedly associated with lower levels of self-reported prejudice. In some situations, however, contact may have little or no association with prejudice. Studies conducted in apartheid South Africa rarely found such an association. Apartheid was overturned in 1994, but there have been few explicit tests of the relationship since then. The present study explored the relation between contact and prejudice in a large (N = 2,599) and diverse nonprobability sample of South Africans. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
4
23
0
3
Order By: Relevance
“…This indicates that more prejudiced individuals are more likely to believe that the other group thinks negatively of them as a member of their group. This has also been found in other South Africa studies (Moholola & Finchilescu, 2006; Tredoux & Finchilescu, this issue). Interestingly, Vorauer et al (1998) found a rather different pattern.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates that more prejudiced individuals are more likely to believe that the other group thinks negatively of them as a member of their group. This has also been found in other South Africa studies (Moholola & Finchilescu, 2006; Tredoux & Finchilescu, this issue). Interestingly, Vorauer et al (1998) found a rather different pattern.…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that crossgroup friendships may indeed be important in bringing about improved intergroup relations and intergroup understanding within the South African context, and highlight the central importance of intergroup emotions in the contact–prejudice relationship. Together with other South African findings (e.g., Tredoux & Finchilescu, this issue) the present research reiterates the importance of multicultural educational environments in South Africa as a means for providing individuals from largely racially homogeneous communities with the opportunity for engaging in positive contacts with outgroup members, as such contacts are regularly associated with more positive intergroup emotions and outgroup attitudes (Pettigrew, 1998). Increased opportunities for contact have been shown to be a significant predictor of actual intergroup contact in European studies (e.g., Turner et al, 2007; but see Alexander & Tredoux, this issue; Dixon & Durrheim, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…More encouragingly, where positive intergroup contacts are reported, they are associated with positive intergroup attitudes (e.g., Dixon et al, this issue; Tredoux & Finchilescu, this issue). Within the context of the present research, one may expect that such contact–prejudice relationships will be stronger for Whites than for Coloureds.…”
Section: The South African Contextmentioning
confidence: 95%
“…During focus group discussions, the majority of students described contact as superficial, infrequent, and limited to the tutorial classroom. Tredoux and Finchilescu (this issue) report similar low frequency and quality of contact for university students. In our study, some group differences were observed.…”
Section: Discussionmentioning
confidence: 71%